Aplikasi Web Commerce sebagai Ruang Praktik Mahasiswa dalam Berwirausaha - Marsinah Dewi Feiyska Nasution; Muhammad Giatman; Ernawati Nazar (Universitas Hamzanwadi, 2021)
Entrepreneurship is one of the subjects that must be taken by students of Universitas Negeri Padang (UNP), including students from Faculty of Tourism and Hospitality. Students sometimes have less interest and motivate in taking entrepreneurship courses in practice because they still only use conventional methods. The purpose of this research is to create a web commerce application that will be used by students as an entrepreneurship practices space. The method that used in making this application is the waterfall model with the SLDC method or a simple software life flow approach. Web commerce application that produced then tested using black box to find out the success of the flow that has been designed, and the black box test results show that the application can run well. The result of this research is a dynamic web-based e-commerce application using the PHP programming language, osCommerce Content Management System (CMS), and MySQL database. This application can be a solution to the problems of conventional entrepreneurial methods and can make students who take entrepreneurship courses more interested in entrepreneurship practices.